Anatomical X-ray study of common opossum (Didelphis marsupialis) in peri-urban areas of Medellín, Colombia - Zapata Muñoz, Jessica (2021)
The aim of this study was to describe the radiological morphology of common opossum (Didelphis marsupialis), establishing the foundation for a correct manipulation and adequate clinical management. The individuals were captured with baited Tomahawk traps in the village of Santa Elena, municipality of Medellín, Colombia. The sex of the animals was identified and the possible presence of pups in the pouch was verified (animals with pups were released). An anesthetic protocol based on xylazine, tiletamine and zolazepam was used and the right lateral, dorsoventral and ventrodorsal X-rays were taken in the axial skeleton (skull, thorax, abdomen and pelvis) and medial-lateral, anteroposterior and dorsal, plantar and palmar in the appendicular skeleton. It was found coincidences with other marsupials in the presence of the ossa marsupialia or epipubic bone, the vertebral formula and the absence of the patella; Furthermore, the presence of structures such as the tympanic bulla is confirmed.